Study of the effects of nutritional restriction on the characteristics of muscle fiber of young bulls - Arrigoni, Mário de Beni; Vieira, Paulo de Figueiredo; Silveira, Antonio Carlos; Furlan, Luiz Roberto; Pai, Vitalino Dal; Costa, Ciniro; Chardulo, Luis Artur Loyola; Oliveira, Henrique Nunes de (Pesquisa Agropecuaria Brasileira, 1998)
The influence of restricting feed intake of young bulls in feedlots was evaluated in terms of structure of muscular fibers and respective areas, sampled by biopsy on the semitendinoso muscle. Sixty six crossbred Simental-Nelore bulls, 8 months old, averaging 220±34.03 kg were submited for 84 days in phase 1 (growing period), to three treatments: ad libitum (AL), restriction + whole soybean (RWS) and restriction + toasted whole soybean (RTS). The level of restriction of feed intake was 23%. Phase 2 was performed by splitting the animals in each treatment in phase 1 in two groups, feeding one with a diet containing soybeans and the other with poultry litter. The results showed that the animals AL presented more white fibers (FG), compared to the RWS and RST and a larger area of these fibers. A greater frequency of red fibers was observed in treatments RWS and RST. The conclusion was that the restriction of feed intake and consequent compensatory growth contributed for modulation of the muscular fibers increasing the frequency of the fast oxidative glycolitic (FOG) in 10.88% and decreasing of the slow oxidative (SO) and FG in 4.81 and 6.90%, respectively, with possible alteration on meat quality.